DINAMIKA KETENAGAKERJAAN DAN PENYERAPAN TENAGA KERJA DI PEDESAAN JAWA (Kasus di Propinsi Jawa Barat, Jawa Tengah dan Jawa Timur) - SUPRIYATI -; SAPTANA -; SUMEDI - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
The last periode, agricultural sector have to burdensome rural labor absorbtion,consequenly decleaning productivity of labor in agricultural sector and wage rate relativelystagnant. This paper obyective to study : (1) labor dinamic in the macro and micro level; (2)variety kind of labor activity and labor supply in wet land rural area; (3) structure of timelabor allocation in household level; (4) trend of wage rate in wet land rural area. Both inmacro and micro level labor absorbtion in agricultural sector each achieved 68 % and 66 %.Total labor absortion by members household about 75 – 127 days (21-35 %) from timeavaibility. Trend of riel wage rate in two provincial (East Java and Central Java) relativelystagnant (1.03 – 2.03 % per years), so in West Java Provincial to decleaning (0.09 %/years).This fact to indicate shown sign labor over supplay in the rural area. Several recomendationto solve this problem are land use optimalization by higher plant intencity; to developefarming diversification, especially high value commodity; land and farming consolidation;and to develope agroindustry based on local raw material.